2018
DOI: 10.1080/02699052.2018.1496481
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for aggression among individuals with moderate to severe acquired brain injury: a systematic review and meta-analysis

Abstract: The differences in outcomes may be related to the differential management of anger expression and anger suppression. CBT shows promise, but further studies with comparator groups are needed before conclusions about its efficacy can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Psychological interventions appear moderately effective (d = −0.46) in populations with ABI (see Byrne and Coetzer, 2016;Iruthayarajah et al, 2018) and mental health disorders (see Ross et al, 2013;Lee and DiGiuseppe, 2018). The majority of these interventions are based on cognitive behavioral therapy (CBT), which include several limitations.…”
Section: Psychological Interventions For Aggressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological interventions appear moderately effective (d = −0.46) in populations with ABI (see Byrne and Coetzer, 2016;Iruthayarajah et al, 2018) and mental health disorders (see Ross et al, 2013;Lee and DiGiuseppe, 2018). The majority of these interventions are based on cognitive behavioral therapy (CBT), which include several limitations.…”
Section: Psychological Interventions For Aggressionmentioning
confidence: 99%
“…Small sample size (e.g., single case studies; n = 1) is a common limitation (Alderman et al, 2013;Ross et al, 2013;Byrne and Coetzer, 2016;Iruthayarajah et al, 2018). Studies in populations with mental health disorders contain larger samples than those with ABI.…”
Section: Psychological Interventions For Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In long-term therapy, antipsychotics have severe side effects such as stroke and increased mortality (58). A review about cognitive behavioural therapy (CBT), a nonpharmacological anger self-management technique, concluded that CBT appears to be an effective tool to control aggression in a population with ABI (59). The results of that review show promise for CBT as a non-pharmacological, safe, psychotherapy alternative to medication use for treatment of aggression after brain injury.…”
Section: Considerations and Implicationsmentioning
confidence: 99%
“…Antipsychotics, which are prescribed for the treatment of psychosis, agitation and aggression, may have adverse effects on cognition and severe side effects in the long-term such as stroke and increased mortality (Ballard, Corbett, Chitramohan, & Aarsland, 2009;Stanislav, 1997). Cognitive behavioural therapy, a non-pharmacological anger self-management technique, appears to be a safe and effective tool to control aggression in a population with ABI as alternative to medication use (Iruthayarajah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%